Analisis Dampak Iklan Produk G2G Terhadap Keputusan Pembelian (Studi Universitas Islam Negeri Jurai Siwo Lampung) - Fikri Rizki Utama; Alika Nuri Syahiroh; Alya Nafiza; Anisa Martha Sujiva; Annisa Adhelia Pratiwi5 (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study explores the influence of digital advertising for G2G skincare products on the behavior and purchasing decisions of Generation Z students at UIN Jusila. Using a descriptive qualitative approach through in-depth interviews, the findings indicate that social media, attractive advertising visuals, influencer marketing, discount and bundling promotions, and the authenticity and transparency of messages play a significant role in shaping perceptions, purchase intention, and loyalty among young consumers. However, advertising exposure can also lead to negative impacts such as impulse buying, social pressure (FOMO), and post-purchase regret. The results of this study provide insights for business practitioners and academics regarding effective and ethical marketing strategies, while emphasizing the importance of digital and financial literacy for students to minimize the negative impacts of digital advertising.